ANALYSIS USING ISO 9241-11 ON STUDENT PORTAL WEBSITE - Achmad, Nofryandi; Luthfiyya, Annisa Nur; Shafira, Dea Mayzura; Wibowo, Agung Satrio; Yulina, Putri; Lestari, Sri (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine the usability of the student website portal which is a portal to support the academic process at a university. A high level of usability indicates a high utilization of the system by users to help them. Usability measurement is carried out using 19 questionnaire questions referring to ISO 9241-11, which are grouped into five usability variables, namely learnability, efficiency, memorability, error, satisfaction. The sample in this study were students using web portals with as many as 69 respondents. The results of this study indicate that users agree that the Siakad website is easy to learn, easy, accessible, and use in a relatively short time. In addition, the results of the study also show that users are neutral in their opinion that the content and menus on the Siakad website are quite easy to remember, the error rate that occurs on the website tends to be low and has also met the expectations and needs of students by displaying the latest data and information and maintaining the privacy of each student.